Fabrication and characterization of multi-walled carbon nanotube incorporated ferromagnetic nanowires with self-formed anti-oxidation layers - Kweon, Soon-Cheol; Kim, Sang Woo (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Ferromagnetic FeCoNi alloy nanowires (NWs) with self-formed anti-oxidation (Si/Al) layers were prepared via electrospinning a sal-gel precursor solution containing Si and Al element and multi-walled carbon nanotubes (MWNTs), and their structures and magnetic properties were investigated. The uniform and narrow-sized MWNTs-magnetic alloy NWs with a well-crystallized bcc (1 1 0) texture of FeCo along the easy axis were formed by introduction of MWNTs acted as a sintering inhibitor during annealing. The coercive field at room temperature increased two times higher than that of MWNT-free magnetic NWs due to the well-developed texture and the small grain size, which is slightly larger than the single domain size within the 10-15 nm range for most magnetic metals. As a result, the highly enhanced ferromagnetic NW mats with a MWNT-incorporated nanowire structure have shown great promise for providing a wide range of potential applications, including magnetic recording and ultrahigh-density magnetic storage devices operating room temperature. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: MAGNETIC-PROPERTIES; EXCHANGE BIAS; NANOFIBERS; FE; COMPOSITE; COBALT; CO; NANOPARTICLES; SHELL